Benefits of Structured After-School Literacy Tutoring by University Students for Struggling Elementary Readers. Issue 2 (4th March 2018) - Lindo, Endia J.; Weiser, Beverly; Cheatham, Jennifer P.; Allor, Jill H.
ABSTRACT: This study examines the effectiveness of minimally trained tutors providing a highly structured tutoring intervention for struggling readers. We screened students in Grades K–6 for participation in an after-school tutoring program. We randomly assigned those students not meeting the benchmark on a reading screening measure to either a tutoring group or a control group. Students in the tutoring group met twice per week across one school year to receive tutoring from non–education major college students participating in a service-learning course. The goal of this study was to determine whether tutors without prior teaching experience or instruction could improve student reading outcomes with minimal training, a structured reading curriculum, and access to ongoing coaching. Tutored students displayed significantly more growth than control students in letter-word identification, decoding, and passage comprehension, with robust effect sizes of 0.99, 1.02, and 0.78, respectively. We discuss the implications and limitations of these findings.